The Interpretation of Nicene Christology at the Council of Alexandria (c. 370) and Its Revision - Włodzimierz Wołyniec (Collectanea Theologica)
Although the Council of Nicaea (325) has already been copiously discussed, the document of the Council of Alexandria (370) still offers a fresh insight into the interpretation of the former Council’s teaching and into its reception. This article is a theological analysis of the conciliar document, written by Athanasius of Alexandria: Letter to the African Bishops against the Arians. The document draws attention to the concept of substance (ousia), which was rejected by the Arians as not biblical. The Council disagreed with the Arians’ claim, presented the biblical foundation of this term and used the formula: “the Son is of the substance of God,” which means that the Son is consubstantial (homoousios) with the Father. Ultimately, the Council of Alexandria agreed on the Homoiousian formula of the Son’s resemblance “in substance” to the Father (kat’ ousian). A revision of the conciliar teaching allows us to discover in God the permanent basis (substance) of life and the Greatest Good (hyparxis), incomparable with other goods (Jer 9:9 and Heb 10:34).